MITOS PEZIARAHAN PANTAI SELATAN MELALUI PERSPEKTIF PSEUDO-ETNOFOTOGRAFI - Purnomo, Aji Susanto Anom (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2024)
The creative process of creating fine-art photographic works so far is considered to have an emphasis on personal artistic expression. This research seeks to present an alternative offer where personal expression and socio-cultural phenomena can be cohesively intertwined and built in the creative process of creating fine-art photographic works. This is answered through the concept of pseudo-ethnophotography. Ethno-photography is an approach in social research that is the trajectory of photographic record and ethnographic narratives. The ethno-photographic method is used to understand society's point of view that gives meaning to a specific cultural phenomenon. Recent developments in the ethnographic approach gave rise to the concept of pseudo-ethnography. The idea arises from a new symptom of artwork creation where an artist descends into a community environment, conducts a brief interview, and then creates artwork from the data obtained. This research then adapts the pseudo-ethnographic approach with an ethno-photography approach to pseudo-ethnophotography. The South Sea entity (Laut Kidul) has a solid and deep-rooted myth for the Javanese. The figure that emerged from the myth is Gusti Kanjeng Ratu Kidul, the ruler of the The South Sea Palace. Parangkusumo Beach is one of the beaches located in the South Sea; Parangkusumo Beach is located in Bantul Regency, Special Region of Yogyakarta. Parangkusumo Beach has a role as a cultural entity that becomes the space of local myths. This myth strengthens the roots of Javanese identity, often known as Kejawen. This research sets out by applying the concept of pseudo-ethnography and adapting it to the pattern of creating photographic art into pseudo-ethnophotography. The stages of research used are literature study, observation, photographic recording, and data analysis. This study aims to offer a point of view that departs from the emic view of the myth of Parangkusumo Beach and its influence on the philosophy of the jawan of pilgrims. This research results in a series of photo works, which are pseudo-ethnophotographic recordings and textual narratives processed from data analysis and personal stories from pilgrims. This research is expected to present an understanding of the Javanese philosophy of the pilgrims who are part of their Javanese identity.